A new route to BCD tricyclic fragment of C19-diterpenoid alkaloids via intramolecular Pauson-Khand reaction followed by anionic 1, 2-migration rearrangement. (13th April 2021) - Yang, Guangguang; Zhu, Mengqian; Zhao, Xin; Lei, Jiang; Xu, Liang
Graphical abstract: Highlights: A bridged BCD rings of C19 -diterpenoid alkaloids has been constructed. An intramolecular Pauson-Khand reaction to form [7-5-5] ring system. An anionic 1, 2-migration rearrangement to generate bicyclo[3.2.1]octane moiety. Abstract: A robust synthetic approach for the rapid assembly of the bridged tricyclic BCD ring system of C19 -diterpenoid alkaloids bearing a characteristic hydroxy group on ring C has been developed. The synthesis features an efficient intramolecular Pauson-Khand reaction and an exclusive anionic 1, 2-migration rearrangement to generate the unique bicyclo[3.2.1]octane moiety of the CD-ring on the seven-membered B-ring.